The impact of demographic changes in Poland on the development of the aesthetic medicine market (Journal of Face Aesthetics, 2023)
The phenomenon of an "aging Polish society" is a multi‑faceted problem which includes, among others, an increase in average life expectancy, an increased proportion of older people in the population, as well as migration to large cities. These changes, which have been taking place for many years, have impacted the development of the aesthetic medicine market. Through analyzing the general population demographics against the demographics of the aesthetic medicine market, we believe that in the coming years there will be an increased demand for aesthetic treatments in people over 50 years of age, especially in offices located in large urban centers.
Keywords: aesthetic medicine; demographic changes in Poland; aesthetic services market; aging society in Europe